The impact of preoperative fasting time on patients undergoing partial nephrectomy and analysis of risk factors for postoperative hemorrhage - Wang, Chunji; Cui, Jiazhao; Gao, Zihui (Frontiers in Surgery, 2024)
ObjectiveThis study investigates the impact of preoperative fasting time on patients undergoing partial nephrectomy and analyzes the risk factors for postoperative hemorrhage to provide clinical reference for physicians treating patients undergoing partial nephrectomy.MethodsA retrospective analysis was conducted on 74 patients who underwent partial nephrectomy for renal tumors between January 2022 and March 2024. Baseline and perioperative data were collected. The effects of long-term and short-term preoperative fasting on patients undergoing partial nephrectomy were compared. Additionally, univariate and multivariate logistic regression analyses were performed to identify risk factors for hemorrhagic complications following partial nephrectomy.ResultsAmong the patients in this study, 26 (35.14%) underwent short-term preoperative fasting, while 48 (64.86%) underwent long-term preoperative fasting. The hemoglobin difference in the short-term fasting group was 21.08 ± 12.44 ml, compared to 13.65 ± 11.69 ml in the long-term fasting group, showing a statistically significant difference (p = 0.020). Differences in serum calcium (p = 0.003), serum magnesium (p = 0.031), and serum phosphorus (p = 0.001) between the short-term and long-term fasting groups were also statistically significant. Univariate and multivariate regression analyses identified the type of surgery (p = 0.050) and preoperative fasting time (p < 0.001) as independent risk factors for postoperative hemorrhage following partial nephrectomy.ConclusionPatients undergoing partial nephrectomy with short-term preoperative fasting experience a more significant decrease in hemoglobin compared to those with long-term fasting. The type of surgery and preoperative fasting time are independent risk factors for postoperative hemorrhage in patients undergoing partial nephrectomy.